Cross-sectional questionnaire-based study: diabetes mellitus patients’ stressors and perceptions towards the disease - May, Win Win; Zanudin, Nurdiyana Khalisah; Soe, May Khin Soe (All India Institute of Medical Sciences, 2019)
This study aimed to identify the stressors among the Type 2 Diabetes Mellitus (T2D) and to investigate the perceptions of the patients towards T2D disease as a continuation from the previous study. A total of 99 patients from Diabetic Clinic in Pekan, Pahang with type 2 diabetes were enrolled in this study as the respondents. T2D patients that came to the clinic to get routine treatment is requested to answer a set of hardcopy questionnaire that consist of perception towards T2D, feeling about Diabetes Mellitus and multi factors related stressors. Study on the perceptions towards T2D, highest positive respond (strongly agree and agree) is P1 (it is burdensome) with 15 and 41 while the lowest positive respond is P3 (it is associated with external factor such as paranormal and environment) with frequency of 5 and 14 respectively. The feeling about DM showed highest positive respond, 59 out of 99 respondents in F1 (feeling thankful) and F2 (feeling stress). Out of twelve stressors, the highest positive responds towards the S10 (regular exercise), S11 (restricted to consume favorite food) and S12 (limited food consumption) represents more than 50 from total of 99 respondents. T2D patients need intensive guidance from the caregiver and the physicians to motivate and prevent diabetes-related distress. .